Epidemiological susceptibility risk and tourist flows around the world. (January 2021) - Mertzanis, Charilaos; Papastathopoulos, Avraam
Abstract: Global tourist flows have increased in recent decades, but so have the outbreak and spread of epidemics, with enormous social and economic costs for the tourism sector. These developments affect the tourists' decisions to travel through their perception of travel risk and safety. Tourists need to assess whether destinations can identify and manage epidemiological risks to improve travel safety. This paper responds to this challenge by constructing an index of epidemiological susceptibility risk using objective information on the quality of health, environmental safety and communications infrastructures, demographics, economic activity, and institutional governance. The index appears to be a significant predictor of inbound tourist flows and occasionally of outbound flows. The effect on inbound flows is stronger in larger countries and weaker for outbound flows. It remains robust after applying sensitivity and endogeneity tests and economic and non-economic controls. The index could potentially provide a useful policy tool for predicting and managing the implications of epidemics on the tourism industry. Highlights: I construct a composite index of epidemiological susceptibility risk (ESR) The ESR index is used to predict tourist flows around the world The study use a cross-country panel data sample The study models the mitigating role of institutions